Use of interferon in prevention and treatment of respiratory viral infections in adults and children - N. D. Yuschuk; O. S. Khadartsev (Лечащий Врач, 2021)
The article analyzes national and foreign publications covering epidemiologic features of influenza and respiratory viral infections. Efficiency of vaccinations against influenza which has been held during the last 17 years, was shown. The results of interferon application, starting from the first years since it was discovered, were presented. The structure of ARVI and influenza morbidity, with allocation of age groups which were mostly involved in the epidemiologic process, was described. The material analysis allows to conclude that, in the period of epidemiologic increase in ARVI morbidity, timely application of recombinant interferon preparations for prevention and treatment allows to reduce influenza and ARVI morbidity, first of all, in organized groups of children and among the contingent under the risk.